2022
DOI: 10.3899/jrheum.210906
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Disease Activity Predicts Achievement of cDAPSA Treatment Targets With Apremilast: Phase III Results in DMARD-naïve Patients With Psoriatic Arthritis

Abstract: Objective Probability of achieving Clinical Disease Activity Index for Psoriatic Arthritis (cDAPSA) treatment targets (remission [REM], low disease activity [LDA]) was evaluated following apremilast monotherapy in disease-modifying anti-rheumatic drug (DMARD)-naive patients with psoriatic arthritis (PsA) based on baseline disease activity. Methods This post hoc probability analysis of PALACE 4, a phase 3, multicenter, randomized, placebo-controlled study, evaluated shifting across cDAPSA categories from baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In that study, female sex was a strong negative predictor of DAPSA response; however, the authors analyzed only a shorter-term endpoint (3 months) and baseline disease activity was not evaluated. On the other hand, similarly to what was observed in our cohort of PsA patients, the post hoc analyses of PALACE 1-3 studies and PALACE 4 study clearly highlighted that the probability of achieving cDAPSA low disease activity or remission at week 52 was greater for patients with moderate versus high disease activity at baseline [7,8].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In that study, female sex was a strong negative predictor of DAPSA response; however, the authors analyzed only a shorter-term endpoint (3 months) and baseline disease activity was not evaluated. On the other hand, similarly to what was observed in our cohort of PsA patients, the post hoc analyses of PALACE 1-3 studies and PALACE 4 study clearly highlighted that the probability of achieving cDAPSA low disease activity or remission at week 52 was greater for patients with moderate versus high disease activity at baseline [7,8].…”
Section: Discussionsupporting
confidence: 86%
“…A direct comparison with the other real-world studies is not possible since they did not report DAPSA response; however, improvements in symptoms were described in 43.5-60.9% of patients [12,13]. Two recent post hoc analyses of the PALACE 1-3 studies and PALACE 4 study reported 52 weeks of cDAPSA low disease activity or remission, respectively, in 39.4% and 44.9% of PsA patients treated with apremilast [7,8]. When comparing these rates to the one reported in our cohort of patients, it appears to be similar, although slightly higher (54.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation